2023
DOI: 10.1590/1984-0462/2023/41/2021357
|View full text |Cite
|
Sign up to set email alerts
|

Effects of slime toy poisoning in children and teenagers

Abstract: Objective: The aim of this study was to identify which types of skin reactions are associated with slime toys and which of their ingredients are most frequently involved in cases of poisoning. Data source: Between January and July 2021, articles were selected using PubMed, SciELO, and LILACS databases. The following descriptors were used: (dermatitis OR rash OR eczema OR inflammation) AND slime. Inclusion criteria were articles available in full, in either Portuguese, English, or Spanish, published between Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Graf's method, although relatively simple and reproducible, requires extensive training for reliable appraisal as the image of the hip must be acquired in a specific spatial plane and the anatomical landmarks must be properly identified [28]. Those requirements can be challenging, especially for less experienced examiners-some studies have demonstrated low levels of intraobserver and interobserver agreement [29].…”
Section: Challenges Of Physician Training In Ddh Care In Brazilmentioning
confidence: 99%
“…Graf's method, although relatively simple and reproducible, requires extensive training for reliable appraisal as the image of the hip must be acquired in a specific spatial plane and the anatomical landmarks must be properly identified [28]. Those requirements can be challenging, especially for less experienced examiners-some studies have demonstrated low levels of intraobserver and interobserver agreement [29].…”
Section: Challenges Of Physician Training In Ddh Care In Brazilmentioning
confidence: 99%
“…It is used as a binder in plaster, adhesives for drywall and wallpaper, and as a coating for concrete and other surfaces [ 11 ]. In addition to the applications mentioned above, PVA is used in a variety of other products, including detergents and soaps, cosmetics and personal care products, adhesives and sealants, paints and coating, toys and games and novel materials and composites [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%